THE EFFECT OF SNOWBALL THROWING AND PROBLEM BASED LEARNING MODELS ON STUDENTS’ SOCIAL SCIENCE LEARNING MOTIVATION AT GRADE IV SUNAN AMPEL DEMAK CLUSTER - Kurniawati; Santoso, Slamet Utomo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to analyze the effect of Snowball Throwing (X1) and Problem Based Learning (X2) models on the students’ social science learning motivation at grade IV elementary schools. The results showed that the snowball throwing model increased the students’ learning motivation based on the value of Sig. (2-tailed) showing that 0.000 <0.05 or t-count 10.660> t-table 1.69236. moreover, problem based learning model also increased the students’ learning motivation based on the value of Sig. (2-tailed) showing that 0.000 <0.05 or t-count 9.603> t-table 1.68957. The results demonstrated that there were differences in the effect of Snowball Throwing model and Problem Based Learning model on students’ social science learning motivation at grade IV in the public elementary schools. This was supported by the mean score of the posttest in experiment 1 which was 74.93 and the mean score of the posttest in experiment 2 which was 71.94.